Luminescence kinetics of crystals LSO co-doped with rare-earth elements - Starzhinsky, N.G.; Sidletskiy, O.Ts.; Grinyov, B.V.; Masalov, A.A.; Malyukin, Yu.V.; Katrunov, K.A.; Zenya, I.M.; Kurtsev, D.A.; Bondar, V.G. (Functional Materials, 2009)
The effect of lutetium oxyorthosilicate (LSO) crystals co-doping with rare-earth elements (Ce, Yb) on the luminescence energy and kinetic parameters has been studied. A significant decrease of light storage (afterglow drop by 10²) is observed at the certain concentrations of activators (Cce ~ 0.1 at. %, Cyb ~ 0.5 at. %). Herein, the luminescence spectral composition and high light yield value are retained, and stability of output characteristics for LSO(Ce, Yb) is improved considerably. Вивчено вплив активування кристалів оксіортосилікату лютецію LSO рідкісноземельними елементами (Се, Yb) на енергетичні та кінетичні параметри люмінесценції. Показано, що при певних концентраціях активуючих домішок (Ссе ~ 0,1 ат. %, Сyb ~ 0,5 ат. %) спостерігається істотне зниження світлозапасання (рівень післясвітіння зменшується приблизно в 10² разів) при збереженні спектрального складу випромінювання та високого світлового виходу з одночасним значним поліпшенням стабільності вихідних характеристик LSO(Ce, Yb). Изучено влияние активирования кристаллов оксиортосиликата лютеция LSO редкоземельными элементами (Се, Yb) на энергетические и кинетические параметры люминесценции. Показано, что при определенных концентрациях активирующих примесей (Ссе ~ 0,1 ат. %, Сyb ~ 0,5 ат. %) наблюдается существенное снижение светозапасания (уровень послесвечения уменьшается примерно в 10²) при сохранении спектрального состава излучения и высокого световыхода с одновременным значительным улучшением стабильности выходных характеристик кристаллов LSO(Ce, Yb).